O sentido da vacina ou quando o prever é um dever The meaning of vaccine or when predicting is a duty - Myriam Bahia Lopes (História, Ciências, Saúde: Manguinhos, 1996)
Partindo da historiografia, analisamos a construção do monumento da medicina científica: a vacina antivariólica. Ao criar e difundir a vacina, a medicina demonstra como a técnica controla a vicia em escala planetária. A grande vitória da medicina científica se funda no seguinte resultado: hoje, a existência do vírus cia varíola depende da vida em laboratório. O movimento antivacinista surge na década de 1870, na Inglaterra, e questiona a adoção universal e obrigatória da vacina antivariólica. Estudamos algumas metáforas e analogias empregadas por médicos e historiadores. Elas nos revelam o processo de construção do fato vacina. From the perspective of historiography, the article analyzes the construction of scientific medicine's major landmark: the small-pox vaccine. When this vaccine was created and widely distributed, the medical field demonstrated how technology controls life on a planetary scale. The great victory of scientific medicine rests on the fact that today the life of the small-pox virus depends upon laboratory conditions. Born in England during the 1870's, the anti-vaccine movement questioned universal, mandatory small-pox vaccination. The article examines some metaphors and analogies used by physicians and historians, revealing the process by which the vaccine, as a phenomenon, was constructed.